Cyclophosphamide enhances the release of tumor exosomes that elicit a specific immune response in vivo in a murine T-cell lymphoma - Cocozza, Federico; Menay, Florencia; Tsacalian, Rodrigo Farid; Elisei, Analia; Sampedro, Pura; Soria, Ivana; Waldner, Claudia Inés; Gravisaco, María José; Mongini, Claudia (Elsevier, 2019)
Exosomes are 60–150 nm small extracellular vesicles (EVs) released by most cells. Tumor-cell-derived exosomes, used as a vaccine, elicit a specific cytotoxic response against tumor cells, usually with a greater immunogenicity than tumor-cell lysates. However, the number of exosomes isolated from culture cells is limited. In recent studies, it was observed that cells respond to different stressor stimuli such as cytotoxic drugs, hypoxia, acidosis, or radiation by increasing the release of EVs. In this study, using the murine LBC T-cell lymphoma, we found that cyclophosphamide significantly increased EVs yield. These EVs express exosome marker proteins such as TSG-101, CD9, CD81, and CD63. Furthermore, similar humoral and cellular immune responses were induced in vivo by EVs isolated from LBC-tumor cells whether they were grown under normal culture conditions (EVs C) or in the presence of cyclophosphamide (EVs CTX). Mice vaccinated either with EVs C or EVs CTX were similarly protected against an intraperitoneal challenge with LBC tumor cells. CD4+ and CD8+ IFN-c secreting cells were induced in immunized mice and a specific cytotoxic cellular immune response was elicited in vitro. These results demonstrate that a Th1 response was induced by immunization with the EVs. Our findings suggest that treatment of tumor cells with cyclophosphamide is a useful method to enhance the secretion of EVs in sensitive cell lines without altering their antitumor properties and thus may be used to produce antigens for future design of cancer vaccines.